Neuromodulation for facial pain - Slavin, Konstantin V. (Progress in neurological surgery / series editor L. Dade Lunsford, 2020)
Neuropathic pain involving the face can be very severe and disabling; often, it is hard to control with conventional means and requires use of unconventional interventions on various parts of the trigeminal nociceptive pathways. For the last 60 years, neuromodulation has been used specifically for the treatment of intractable pain in different parts of the human body, including the face and head region. Despite such a long history and existence of many neuromodulation targets, there has not been a dedicated book that would summarize the entire spectrum of neuromodulation approaches that have been - and still are - used for treatment of facial pain. This book begins with dedicated chapters on classification of facial pain and anatomy of facial pain pathways and then dives into specific applications of neuromodulation starting from the periphery all the way to cerebral centers of pain processing, covering both invasive and non-invasive approaches. Written by experts from all over the world, the book offers an up-to-date comprehensive summary of neuromodulation techniques and modalities, providing the readers with a practical guide on clinical details of patient selection, modulation parameters, procedural details, and expected outcomes that may be used in daily clinical practice dealing with most difficult facial pain conditions.